ABO-incompatible heart transplantation in children—a systematic review of current practice - Beeman, Arun (Indian J Thorac Cardiovasc Surg, 2020)
Pediatric heart transplantation has significantly improved in the survival of children with cardiomyopathy and/or complex congenital heart defects. With the increasing number of children needing transplantation, there is a growing demand for the organ, making it harder to cope with the increasing number of children on the waiting list. One of the advances that helped reduce the waiting list mortality significantly is the ability to transplant children from donors with ABO incompatibility. Modification of perfusion abilities and management of donor organ improves outcome in this select population, making ABO-incompatible transplantation an attractive option in the wider armamentarium available for pushing boundaries in these children without impacting on outcomes.